The Effect of the Montessori Method on Children's Ability to Sort Patterns and Fine Motor Skills in Kindergarten AL Muhajirin - Hermildawati, Hermildawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Montessori method on students’ sort patterns and fine motor skills at TK Al Muhajirin. The background of this research is based on the low sort patterns and fine motor skills of students. This research employed a equivalent-experimental method with a pretest-posttest control group design. The research subjects consisted of two class at the B level of TK AL Muhajirin, namely the experimental group treated with the Montessori method and the control group using the demonstration method. The research instruments were in observation sheets, which were analyzed using parametric statistical tests (t-tests) to determine the differences in sort patterns and fine motor skills between the two groups. The results of the analysis showed a statistically significant difference between the experimental group and the control group, with students in learning using montessori method showed a higher increase in sort patterns and fine motor abilities. Therefore, it can be concluded that the application of the montessori method has a positive and significant effect on enhancing students' sort patterns and fine motor skills at TK AL Muhajirin.